Sub-alpine periglacial morphology of thufur on the southern rim of Vlasina Lake, Serbia - Milošević, Marko V.; Kovačević-Majkić, Jelena; Ćalić, Jelena; Milivojević, Milovan (ERDKUNDE, 2015)
The paper elaborates on the occurrences of thufur (earth hummocks, pounus) in a sub-alpine periglacial environment of the Vlasina Lake (1210 m a.s.l.) in south-eastern Serbia. Field examination encompassed 8 sites at the southern rim of the lake, at altitudes from 1220 m to 1274 m, where 240 thufur were measured for height (av=32 cm) and diameter (av=51 cm). Parameters of topography (relative heights, gradient, aspect) and overall morphology are analysed as well. The lake basin represents an area of cool air accumulation and temperature inversions. The upper limit of this zone, where 7 out of the 8 studied sites are situated, is the highest closed contour at 1243 m. Analysis of the relation between lithology, morphology and groundwater drainage showed that thufur on poorly drained sites are well developed, whereas the sites with good drainage are characterized by relatively small thufur. Detailed study of the height/diameter relation enabled differentiation between three morphological types of circular thufur: prolate spherical domes, hemispherical domes and oblate spherical domes.